Nightmares (Bangungut) is the Leading Cause of Sudden Unexplained Nocturnal Death among Adults( SUNDS), its Risk Factors, and Solution. A Review of Literature (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: Background: Nightmare(NM) and its various names is a well known phenomena In different societies The synonyms (Bangungut) in Philippine is colloquial